Brain Mechanisms for Concept Formation Based Exclusively on the Visual Modality - Anna P. Kamaniuk; Alexander V. Vartanov (Lomonosov Moscow State University, 2024)
Background. The problem of concept formation in the visual modality remains largely unexplored. There are many studies on the formation of verbal concepts in the learning process. However, it has not yet been fully investigated how concept formation occurs in conditions when both the signified and the signifier (sign) are represented only in the visual modality and what brain mechanisms are involved in this process. Objectives. The aim of the present work was to identify the brain mechanisms of visual concepts formation, on the basis of EEG registration with subsequent localization of the sources of electrical activity. Another task is to evaluate the possibility of actualizing the process of indirect learning in the formation of visual concepts. Study Participants. 26 Russian-speaking subjects without neurological disorders: 10 males and 16 females (aged 18 to 40 years, mean age 22.92 years, SD = 6.38) participated in the study. Methods. Chinese hieroglyphs, unfamiliar to the subjects, were taken as signs. The designated ones were emoticons (schematic faces expressing various emotions). A total of 10 pairs of stimuli sign-designated were presented. A 19-channel electroencephalogram (EEG) was recorded in three successive series: 1) the initial perception of hieroglyphic signs without assigning them a category; 2) categorization of these signs in the process of associative learning, with only 8 designating stimuli-signs directly associated with the designated stimulus, while 2 stimuli-signs were never associated with the stimulus-designator, their meaning was established indirectly; 3) subsequent perception of signs with the meaning already assigned to them. All stimuli were presented to the subjects visually. A new method of localization of brain activity, "Virtually implanted electrode", developed by A.V. Vartanov (patent RU No. 2 785 268) was applied. Results. The analysis of the subjects' responses showed that during the learning process all signs (including those formed indirectly) were assigned a certain meaning (designated). Differences in event-related potentials (ERP) were found in leads C3 and CZ. Significant differences in ERP as a result of learning were revealed in a number of brain structures. It was found that a number of functional connections between the left area of the secondary visual cortex and the right part of the cerebellum changed significantly as a result of learning. Conclusions. The development of visual categories is ensured by the coordinated work of the right part of the cerebellum, parahippocampal gyrus and primary visual cortex, which is confirmed by the discovered differences in the corresponding ERPs.